Chemically Modified Extracellular Vesicles and Applications in Radiolabeling and Drug Delivery - Elisa-Racky N'Diaye; Nicola Salvatore Orefice; Catherine Ghezzi; Ahcène Boumendjel (MDPI AG, 2022)
Extracellular vesicles (EVs) have been exploited as bio-inspired drug delivery systems (DDS) in the biomedical field. EVs have more advantages than synthetic nanoparticles: they are naturally equipped to cross extra- and intra-cellular barriers. Furthermore, they can deliver functional biomolecules from one cell to another even far away in the body. These advantages, along with obtained promising in vivo results, clearly evidenced the potential of EVs in drug delivery. Nevertheless, due to the difficulties of finding a chemical approach that is coherent with EVs' rational clinical therapeutic use, those in the drug delivery community are expecting more from EVs' use. Therefore, this review gathered knowledge of the current chemical approaches dealing with the conjugation of EVs for drugs and radiotracers.